2020
DOI: 10.1002/nafm.10416
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Latitude, Season, and Temperature on Lake Sturgeon Movement

Abstract: Ecologists have a limited understanding of the rangewide variation in movement behavior in freshwater fishes, but recent expansion of biotelemetry allows biologists to investigate how fish movement can help to predict behavioral shifts in response to changing environments. The Lake Sturgeon Acipenser fulvescens is a wide‐ranging, migratory, coolwater species, making it a candidate species for studying patterns in movement ecology. We conducted a literature review and meta‐analysis of seasonal movement data com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 65 publications
(107 reference statements)
2
20
0
Order By: Relevance
“…For migratory fish like Lake Sturgeon, hydrologic regulation may impede movements important to maintaining energy stores and accessing spawning sites (Baras & Lucas, 2001). Furthermore, recognition is increasing that Lake Sturgeon and other freshwater fish species exhibit intra‐specific and intra‐population variation in migratory behaviour that may have regional management implications (Chapman et al, 2012; Moore et al, 2020). Therefore, we conducted the first study to directly compare Lake Sturgeon movement in two rivers with varying degrees of hydrologic regulation within a range‐edge population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For migratory fish like Lake Sturgeon, hydrologic regulation may impede movements important to maintaining energy stores and accessing spawning sites (Baras & Lucas, 2001). Furthermore, recognition is increasing that Lake Sturgeon and other freshwater fish species exhibit intra‐specific and intra‐population variation in migratory behaviour that may have regional management implications (Chapman et al, 2012; Moore et al, 2020). Therefore, we conducted the first study to directly compare Lake Sturgeon movement in two rivers with varying degrees of hydrologic regulation within a range‐edge population.…”
Section: Discussionmentioning
confidence: 99%
“…Triggered by temperature and flow, reproductive adults may migrate up to 150 km to reproduce at rocky rapids in tributaries that oxygenate their adhesive demersal eggs (Auer, 1996a; Auer, 1996b; Forsythe et al, 2012; McKinley et al, 1998; Shaw et al, 2013) and subsequently retreat downstream to lakes or larger rivers (Peterson et al, 2007). Water temperatures above 28°C in populations near the southern range margin may cause thermal stress, periods of inactivity and arrested growth (Bezold & Peterson, 2008; Lyons & Stewart, 2014; Moore et al, 2020), whereas Lake Sturgeon also often remain sedentary in deep waters in colder months (Hay‐Chmielewski, 1987; Rusak & Mosindy, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a study conducted on subadult lake sturgeon in the St. Lawrence River reported that dispersal from the tagging location usually did not exceed 48 km and was frequently less than 16 km (Magnin & Beaulieu, 1960). In a metaanalysis of 38 lake sturgeon telemetry studies in North America, Moore et al (2021) showed that movement distances of lake sturgeon are highly variable and have large seasonal differences. Their meta-analysis indicated that lake sturgeon movement ranged between 100 and 1,500 m per day in the spring, and less than 400 m per day in the late summer and fall (Moore et al, 2021).…”
Section: This Proportion Is Considerably Lower Than What Has Been Reportedmentioning
confidence: 99%
“…In a metaanalysis of 38 lake sturgeon telemetry studies in North America, Moore et al (2021) showed that movement distances of lake sturgeon are highly variable and have large seasonal differences. Their meta-analysis indicated that lake sturgeon movement ranged between 100 and 1,500 m per day in the spring, and less than 400 m per day in the late summer and fall (Moore et al, 2021). However, movement patterns of lake sturgeon in brackish water estuaries are not well studied.…”
Section: This Proportion Is Considerably Lower Than What Has Been Reportedmentioning
confidence: 99%